Introduction to health care & careers - DeLaet, Roxann (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"Introduction to Health Care & Careers provides students beginning their health care education with the fundamentals they need to develop their personal and professional skills, understand their chosen profession, and succeed in the world of health care. It meets the growing market demand for a book that gives the best of both worlds--skill development and career choice information. The text begins with today's health care system, health care economics, and law and ethics, providing important context for the personal, professional, and workplace skills that follow. From there, students move on to an overview of careers in health care and detailed profiles of the most in-demand professions. The book closes with brief chapters on anatomy and physiology to prepare students for the rest of their health care education. With its student friendly approach, Introduction to Health Care & Careers is the essential resource for introductory health care courses, striking the perfect balance between skill development and up-to-date career choice information-everything health care students need to succeed."--Provided by publisher.